2016
DOI: 10.1038/mto.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DAI by an oncolytic vaccinia virus boosts the immunogenicity of the virus and enhances antitumor immunity

Abstract: In oncolytic virotherapy, the ability of the virus to activate the immune system is a key attribute with regard to long-term antitumor effects. Vaccinia viruses bear one of the strongest oncolytic activities among all oncolytic viruses. However, its capacity for stimulation of antitumor immunity is not optimal, mainly due to its immunosuppressive nature. To overcome this problem, we developed an oncolytic VV that expresses intracellular pattern recognition receptor DNA-dependent activator of IFN-regulatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…VV-TRIF showed improved antitumor efficacy in colon and renal tumor models compared to VV-GM-CSF (Pexa-Vec). Similar results were obtained using intracellular pattern recognition receptor DNA-dependent activator of IFN-regulatory factors (DAI) as an vectorized immune modulator [103]. These studies show that the antitumor immune response can be switched from Th2 to Th1 by manipulating intracellular pathogen receptor signaling pathways in tumor cells.…”
Section: Pathogen Receptorssupporting
confidence: 66%
“…VV-TRIF showed improved antitumor efficacy in colon and renal tumor models compared to VV-GM-CSF (Pexa-Vec). Similar results were obtained using intracellular pattern recognition receptor DNA-dependent activator of IFN-regulatory factors (DAI) as an vectorized immune modulator [103]. These studies show that the antitumor immune response can be switched from Th2 to Th1 by manipulating intracellular pathogen receptor signaling pathways in tumor cells.…”
Section: Pathogen Receptorssupporting
confidence: 66%
“…Consistent with previous works, our established rechallenge and bilateral tumor-bearing models showed that oHSV2 caused a systemic long-term antitumor immune response while exerting a direct antitumor effect. 23 This tumor-specific immune response effectively inhibited both secondary identical tumorigenesis and the growth of distant nontreated tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Oncolytic viruses have been tested in preclinical studies and in numerous clinical trials against various tumor types, have a tolerable safety profile, and show varying degrees of efficacy. 8,[10][11][12][31][32][33][34][35][36][37][38][39][40] Their advantages include lysis of infected tumor cells, release of tumor antigens in an immunogenic milieu, and viral infection of adjacent tumor cells. In addition, Figure 5.…”
Section: Discussionmentioning
confidence: 99%